Characterization of synbiotic ice cream made with probiotic yeast Saccharomyces boulardii CNCM I-745 in combination with inulin. (April 2021) - Sarwar, Abid; Aziz, Tariq; Al-Dalali, Sam; Zhang, Jian; Din, Jalal ud; Chen, Chao; Cao, Yongqiang; Fatima, Hina; Yang, Zhennai
Abstract: The effects of probiotic yeast Saccharomyces boulardii CNCM I-745 in combination with prebiotic inulin on the probiotic survivability, physiochemical properties and stability of ice cream were evaluated. Addition of inulin increased the viability of S. boulardii CNCM I-745 with viable count of 6.16 log CFU/g in the synbiotic ice cream after 120 d of storage. Fermentation with the probiotic yeast and Lactobacillus-Streptococcus (LS) caused significantly (p < 0.05) decreased firmness of ice cream samples, S1-Pro (510.2g) and S2-Pro-LS (492.7g), compared with that (545.9g) of the control S0. However, addition of 1% and 2% inulin recovered the firmness of the synbiotic ice cream, S3-Syn1 (535.3g) and S4-Syn2 (548.3g), respectively. Synbiotic ice cream had improved melting property and stability as indicated by measurements of particle size, zeta potential and multiple light scattering. Among 27 volatile compounds identified in different ice cream formulations, the synbiotic ice-cream with 2% inulin contained higher concentrations (3983 μg/L) than S1-Pro (1479 μg/L) and S0-control (616.4 μg/L) ice creams. The synbiotic ice cream of this study represents a potential novel functional product containing probiotic yeast and prebiotic inulin. Highlights: Saccharomyces boulardii and inulin (prebiotic) were used to fortify ice-cream. Inulin improved physicochemical and survival of yeast in synbiotic ice-cream. Zeta potential and Turbiscan stability index confirmed stability synbiotic ice cream. Synbiotic ice cream contained more volatile compounds. Synbiotic ice cream-maintained viability of S. boulardii (6.16 log CFU/g) even after 120 days of freeze storage.